Analisis Pengaruh Cognitive Image, Affective Image, Dan Unique Image Terhadap Keputusan Berkunjung Dengan Minat Kunjungan Sebagai Mediasi (Studi Pada Objek Wisata Pantai Menganti Kebumen) - Wardhana, Abimanyu Wisnu; Munas, Bambang (Faculty of Economics and Business | Universitas Diponegoro, 2024)
The purpose of this study to analyze the effect of cognitive image, affective image and unique image on interest of visits and the impact on visiting decision. The population used in this study are tourist who had visited the Menganti Beach tourist attraction, Kebumen Regency, at least once. The number of samples used in this study were 110 respondents. The method of data collection is done through a questionnaire. This study uses Structural Equation Modeling (SEM) analysis techniques with AMOS 22.0 analysis tool. The results of this study show that cognitive image has a positive and significant effect on interest of visits, cognitive image does not have significant on visiting decision, affective image has a positive and significant effect on interest of visits, affective image does not have significant on visiting decision, unique image has a positive and significant effect on interest of visits, unique image does not have significant on visiting decision, and interest of visits has a positive and significant effect on visiting decision.Keywords: Expectancy Theory, Cognitive Image, Affective Image, Unique Image, Visit Intention, Visiting Decision